Volume 3: 19th International Conference on Design Theory and Methodology; 1st International Conference on Micro- And Nanosystem 2007
DOI: 10.1115/detc2007-35541
|View full text |Cite
|
Sign up to set email alerts
|

Review, Modelling and Simulation of Two-Mode Hybrid Vehicle Architecture

Abstract: Hybrid vehicle technology is beginning to make a significant mark in the automotive industry, most notably by the Toyota Prius THS-II and its one-mode technology, but also by two-mode architectures recently introduced. GM-Allison, Renault, and the Timken Company have attempted to capitalize on the advantages over simpler series and parallel architectures that the series-parallel configuration confers on the Prius while also improving the design by allowing the powertrain configuration to physically shift and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…From the above analysis, three main aspects are found to compensate the 534kJ less energy output from the engine of the MMT vehicle: (1) 37.62kJ more braking regenerative energy; (2) 280kJ less loss in the electric machine units; and (3) 225kJ less loss in the battery. Thus, due to the limitation of the single electric machine structure, the MMT vehicle operates the engine in relative lower efficiency region, but achieves less loss from the electric power devices; on the contrary, the "THS II-like" vehicle operates the engine in ideally high efficiency region, but produces more loss from the electric power devices.…”
Section: Synthesis Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…From the above analysis, three main aspects are found to compensate the 534kJ less energy output from the engine of the MMT vehicle: (1) 37.62kJ more braking regenerative energy; (2) 280kJ less loss in the electric machine units; and (3) 225kJ less loss in the battery. Thus, due to the limitation of the single electric machine structure, the MMT vehicle operates the engine in relative lower efficiency region, but achieves less loss from the electric power devices; on the contrary, the "THS II-like" vehicle operates the engine in ideally high efficiency region, but produces more loss from the electric power devices.…”
Section: Synthesis Analysismentioning
confidence: 99%
“…Hybrid electric vehicles (HEVs), as one kind of new generation vehicles, are considered to offer the best promise in the short to mid-term [1] to solve the problem of global energy shortage and environment pollution. For most of the currently developed HEVs, such as TOYOTA THS, Ford FHS, GM AHS, etc, two electric machines (EMs) are commonly used [2][3][4][5]. One of the two EMs works mostly as a driving motor, the other as a generator.…”
Section: Introductionmentioning
confidence: 99%
“…There are varies types of HEV topologies that have been designed by the automotive companies; such as Toyota's series-parallel hybrid system (THS) [1], Honda's single axle parallel integrated motor assist system [2] and General Motors (GM) two-mode hybrid system (Advanced Hybrid System 2 or ASH2) [3]. In addition to major automotive companies many research laboratories have proposed different topologies to achieve best overall efficiency from the drive train.…”
Section: Drive Train Topologies Of Hybrid Electric Vehiclesmentioning
confidence: 99%
“…Both the output split and the input split systems have only one mechanical point. 7 J Kim has made detailed comparisons between the transmission efficiencies of dual planetary structure and single planetary structure. It is indicated that the ideal transmission ratio is easier to be obtained by the dual planetary structure, which leads to the high operation efficiency range of the vehicle.…”
Section: Introductionmentioning
confidence: 99%